Quality Of Impressions Made For Fixed Partial Denture By Dental Students - A, SUBASHRI.; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2021)
An impression is a negative replica or copy in reverse of the surface of an object. Impression materials in the market are classified by various methods: chemical type, physical properties and viscosities. The aim of the study was to evaluate the quality of impressions made for fixed prostheses by undergraduate and postgraduate students.A total of 875 impressions photographs were analysed based on 10 parameters. The parameters were voids on finish line, lack of wash material, inadequate tray retention etc. They were given scores based on the outcomes, as unacceptable, acceptable and good. The results were recorded and tabulated. Various tests were performed using SPSS software to gain the correlation. The most common errors found among them were the lack of flash, followed by improper tray pressure, voids on the preparation, lack of material, improper fusion of materials. Increased errors were found at the finish line and the presence of blood in impression surfaces were also observed.The quality of impression making by the postgraduate students were better than undergraduates